2011
DOI: 10.1071/an10122
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative behavioural assessment and quantitative physiological measurement of cattle naïve and habituated to road transport

Abstract: The present study examined whether observers could distinguish between cattle that are naïve to road transport and the same cattle after becoming more habituated to transport. The behavioural expression of cattle was assessed through the method of qualitative behavioural assessment (QBA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 34 publications
5
92
0
6
Order By: Relevance
“…QBA terms showed significant correlations with animal based welfare parameters, such as physiological parameters (Stockman et al 2011) and quantitative ethograms (Rutherford et al 2012;Rousing and Wemelsfelder 2006). QBA is thereby increasingly applied to assess animal welfare (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QBA terms showed significant correlations with animal based welfare parameters, such as physiological parameters (Stockman et al 2011) and quantitative ethograms (Rutherford et al 2012;Rousing and Wemelsfelder 2006). QBA is thereby increasingly applied to assess animal welfare (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, QBA has been designed to assess animal welfare, and has as such been applied to a wide range of species (pigs: Wemelsfelder et al 2000;Wemelsfelder et al 2001;Rutherford et al 2012; dairy and beef cattle: Rousing and Wemelsfelder 2006;Stockman et al 2011;sheep: Phythian et al 2013;horses: Napolitano et al 2008;and dogs: Walker et al 2010). QBA terms showed significant correlations with animal based welfare parameters, such as physiological parameters (Stockman et al 2011) and quantitative ethograms (Rutherford et al 2012;Rousing and Wemelsfelder 2006).…”
Section: Discussionmentioning
confidence: 99%
“…QBA can take one of two forms, the free-choice profiling format where descriptive terms are elicited from the assessors themselves, or the fixed term format where designated terms are rated by assessors according to what they find, and is the form found in the Welfare Quality ® protocols. Compared to the free-choice profiling format, where QBA has been associated with physiological welfare indicators in cattle and steers (Stockman et al, 2011 and, and induced emotional states in pigs (Rutherford et al, 2012), QBA as part of the Welfare Quality ® protocol has not been found to be associated with other measures in veal calves (Brscic et al, 2009), or beef cattle (Kirchner et al, 2012). In terms of inter-assessor agreement, the evidence is also mixed for the fixed term format with high levels of inter-observer agreement having been reported in sheep (Phythian et al, 2013), but only 'slight to moderate' agreement for Welfare Quality ® QBA in dairy cows (Bokkers et al, 2012).…”
Section: Heath Browne Mullan and Mainmentioning
confidence: 99%
“…These data are analysed by Generalised Procrustes Analysis (GPA), which identifies common patterns in the use of descriptive terms, followed by a Principal Components Analysis (PCA) to simplify the data into two or three main dimensions. QBA scores generated through the FCP methodology have been validated against physiological parameters (Stockman et al, 2011;2012;Wickham et al, 2012; as well as quantitative behavioural measurements (Napolitano et al, 2008;Stockman et al, 2014). …”
Section: Introductionmentioning
confidence: 99%